Effect of seepage condition in geological stratification on thermal response test analysis of borehole heat exchanger. (March 2023) - Zhang, Changxing; Lu, Xizheng; Liu, Yufeng; Lu, Jiahui; Sun, Shicai
Abstract: Determination of ground thermal properties is the prerequisites for the design of ground-coupled heat pump systems (GCHPs), and it is crucial for evaluating the thermal performance of borehole heat exchangers (BHEs). These parameters are usually obtained by in-situ thermal response test (TRT) based on infinite line source model (ILSM). Though the effect of the groundwater flow on the estimation of ground thermal parameters is considered in homogenous ILSM, the estimated deviation can be enlarged as seepage condition varies based on the BHE model in practical geological stratification. Based on the developed numerical layered seepage BHE model (NLSBM), this paper evaluates the effects of seepage location and seepage velocity on estimated accuracy of borehole thermal resistance and ground thermal conductivity. Relative error (RE) between effective thermal conductivity λ eff and the thickness-weighted thermal conductivity λ TW will be up to 30.5% with the increase of the thickness of the seepage layer. The relative error between λ eff and λ TW increases from 5.3% to 93.5% when seepage velocity changes from 1 × 10 −6 m/s to 1 × 10 −4 m/s. The minimum RE between borehole thermal resistance R b, NLSBM and effective borehole thermal resistance R b, eff is still up to 37% when seepage locates in the 5th layer. With the increase of the seepage velocity, the RE between R b, eff and R b, NLSBM is enlarged, and the minimum RE is up to 29.4% corresponding to the lowest seepage velocity of 1 × 10 −4 m/s. The change of seepage velocity or seepage location has little effect on R b, NLSBM, and the highest RE is only 0.2%.